EFEKTIVITAS KERJA PENYULUH PERTANIAN LAPANGAN DI WILAYAH UPT BALAI PENYULUHAN PERTANIAN PERIKANAN DAN KEHUTANAN KABUPATEN SLEMAN - , RINA INDRAWATI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research was done in UPT BP3K, Sleman Regency. The institution is divided into eight units of extension technical services consisted of area I in Moyudan, area II in Godean, area III in Seyegan, area IV in Sleman, area V in Pakem, area VI in Cangkringan, area VII in Berbah, and area VIII in Prambanan. This research aims to understand the work effectivity of field agricultural extension workers in holding a counseling based on the main task and its function and knowing the factors influenced the work effectivity of field agricultural extension workers in Sleman Regency. The methods used in this research is descriptive analytical approach by applying to quantitative methods and the survey. The selection of extension workers was carried out by sensus. Total respondents were 60 of field agricultural extension workers (PPL), which are 41 of food crops, horticulture extension workers, and 19 of farm extension workers from each institution which includes 7 PPL in the region I Moyudan, 8 PPL in the region II Godean, 12 PPL in the region III Seyegan, 7 PPL in the region IV Sleman, 6 PPL in Region V Pakem, 8 PPL in the region VI Ngemplak, 5 PPL in Region VII Berbah, and 7 PPL in the region VIII Prambanan. Methods of analysis used are the test of proportions and a simple linear regression analysis. The results showed that of 68,33% stated that the effectiveness of extension workers can be categorized as well perform and extension workers who have a high effectiveness is 31,67%. The effectiveness of agricultural extension workers work with score low (<50%) in the professional development that includes on making publication of agricultural scientific papers, scientific papers that are not published in book form, and scientific writings disseminated in the form of media. Education and motivation positively influenced toward the effectiveness of field agricultural extension workers. Factors which do not significantly affecting the real effectiveness of field agricultural extension workers are age, sex, experiences, training, type of commodity, work area, and the number of farmers group that built.